2020
DOI: 10.1182/blood.2020005998
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gemtuzumab ozogamicin on MRD and relapse risk in patients with NPM1-mutated AML: results from the AMLSG 09-09 trial

Abstract: Monitoring of measurable residual disease (MRD) provides prognostic information in patients with Nucleophosmin1 mutated (NPM1mut) acute myeloid leukemia (AML) and represents a powerful tool to evaluate treatment effects within clinical trials. We determined NPM1mut transcript levels (TL) by RQ-PCR and evaluated the prognostic impact of NPM1mut MRD and the effect of gemtuzumab ozogamicin (GO) on NPM1mut TL and the cumulative incidence of relapse (CIR) in patients with NPM1mut AML enrolled in the randomized phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 31 publications
3
59
0
1
Order By: Relevance
“…The serial acquirement of somatic mutations in myeloid clone(s) was described as the multistep pathogenesis of AML. Several lines of evidence prove that NPM1 mutations are responsible for the definitive acute leukemic transformation, therefore considered as leukemia founder mutations: (i) NPM1 mutations are completely absent in the population without hematological malignancies even at a higher age [ [30][31][32][33][34][35][36][37][38][39]. The long observational period in our study allowed us to detect late AML relapses.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The serial acquirement of somatic mutations in myeloid clone(s) was described as the multistep pathogenesis of AML. Several lines of evidence prove that NPM1 mutations are responsible for the definitive acute leukemic transformation, therefore considered as leukemia founder mutations: (i) NPM1 mutations are completely absent in the population without hematological malignancies even at a higher age [ [30][31][32][33][34][35][36][37][38][39]. The long observational period in our study allowed us to detect late AML relapses.…”
Section: Discussionmentioning
confidence: 77%
“…We were unable to test large number of RNA samples, which is a major limitation of our retrospective study. Ivey et al [57] demonstrated that RNA-MRD positivity in PB after induction (2 cycles) corresponded to higher cumulative incidence of relapse (MRC17 trial 3-year CIR: 82% versus 30%), similarly Balsat et al [58] (ALFA-0702 trial: 2-year CIR: 55% versus 21%); Hubmann et al [62] less than 3log-reduction in BM RNA-MRD (AMLCG 1999(AMLCG , 2004(AMLCG and 2008 trial: 2-year CIR 77.8% versus 26.4%,); Kapp-Schwoerer et al [34] less than 3-log 10 BM or PB RNA-MRD (AMLSG 09-09 trial 4-year CIR BM: 60% versus 28.5%; PB: 62.5% versus 33.9%). On the DNA level, we also observed that MRD positivity (less than 3log reduction) was associated with adverse outcome, and DNA-MRD after induction therapy is capable to identify high-risk NPM1 mut patients.…”
Section: Plos Onementioning
confidence: 81%
See 1 more Smart Citation
“…AML achieving CR is known to be associated with a lower relapse risk. It can be considered a broad predictive biomarker useful to guide the patient's postremission management [41][42][43][44][45]. Thus, the ELN consensus recommends molecular MRD assessments for NPM1 mutations, RUNX1-RUNX1T1, CBFB-MYH11, and PML-RARA fusion transcripts at diagnosis, after two cycles of induction/consolidation therapy, and every 3 months, for 24 months after the end of treatment [4].…”
Section: Mrd-negativity Assessed By Real Time Quantitative Polymerase Chain Reaction (Rt-qpcr) In Patients Withmentioning
confidence: 99%
“…EFS has been accepted as primary endpoint for the approval of GO in rst line therapy in AML by the FDA and EMA [48]. EFS compared to OS provides the advantage to be measurable earlier and to be directly linked to the treatment under investigation [40][41][42][43][44][45][46][47][48][49][50][51]. In contrast to overall survival, where death is the only event of interest, EFS also includes failure to obtain complete remission and relapse from complete remission.…”
Section: Mrd-negativity Assessed By Real Time Quantitative Polymerase Chain Reaction (Rt-qpcr) In Patients Withmentioning
confidence: 99%